Tinjauan Hukum Pidana Perjudian Berjenis Slot Berbasis Media Elektronik - Hafidu, Akbar Al; Marwiyah, Siti; Hartoyo, Hartoyo; Sidarta, Dudik Djaja (UNES Law Review, 2023)
In this type of online gambling, players must first choose a betting table before entering and choosing one of the many options available. Therefore, the loser will pay the bet according to the agreed amount. The formulation of the research problems are as follows: 1) How is electronic slot gambling regulated in criminal law? 2) Is it possible to bring charges against online gambling actors under the Information and Electronic Transactions (ITE) Act?. This research uses normative research methodology and data collection strategies for literature studies. According to the findings of his study, the Criminal Code does not clearly regulate the rules for electronic-based slot gambling, but the regulatory changes have provided a legal framework for the ITE Law. As a result, it is certain that online gambling players will face sanctions based on Law Number 19 of 2016 concerning Electronic Information and Transactions, namely Law Number 19 of 2016 concerning Electronic Information and Transactions.